Efektivitas Manajemen Pelayanan Sosial dalam Penanganan Lansia Terlantar di Kota Medan - Arifah Ulayya; Rangga Wijaya; Rio Riswanto Simanjuntak; Ezra Azzahra; Aleeka Jasmine; Hairani Hairani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the effectiveness of social service management in handling neglected elderly in Medan City. The phenomenon of neglected elderly has become a complex social problem along with the increasing number of elderly population and changes in family structure in urban areas. Medan City as the third largest metropolitan city in Indonesia faces challenges in providing optimal social services for neglected elderly. This study uses a qualitative research method with a library research approach. Data collection was carried out through a literature review of various relevant library sources, including scientific journals, books, research reports, policy documents, and official publications of related agencies. Data analysis used content analysis techniques to identify patterns and themes related to the effectiveness of social service management for neglected elderly. The results of the study indicate that social service management in Medan City has not been fully effective in handling neglected elderly. In terms of planning, there are still limitations in mapping and recording neglected elderly data. In terms of organization, coordination between agencies is still weak. Program implementation faces constraints of budget and human resource limitations. The monitoring and evaluation system has not been running optimally. Supporting factors include local government commitment, availability of regulations, and community participation. While inhibiting factors include budget constraints, lack of professional staff, and minimal cross-sector coordination. This study recommends the need to strengthen the social service management system through increasing human resource capacity, optimizing the budget, and strengthening cross-sector coordination to improve the effectiveness of handling the elderly in Medan City.